Efeito do material particulado atmosférico sedimentável oriundo de área industrial siderúrgica em órgãos do robalo-peva (Centropomus parallelus): bioconcentração, estresse oxidativo e histopatologias - Monteiro, Rafaella (2023)
The release of metallic smoke by metallurgical industries contaminates the air and water environment. The increase of metals in the aquatic environment can develop imbalance and pathologies in organisms. In this context, the aim of this study was to evaluate the bioconcentration of metals present in sedimentable atmospheric particulate matter (MPASe), such as antioxidant responses and histopathological changes in gills, hepatopancreas, kidneys and muscles of estuarine fat snook fish, Centropomus parallelus. The fish were exposed to environmentally relevant concentrations (0.0; 0.01; 0.1 and 1g L-1 of MPASe) for 96 hours, in a static system. In the four organs, the activity of superoxide dismutase (SOD) was determined, except muscle, catalase (CAT), glutathione peroxidase (GPx), glutathione-S-transferase (GST), the level of reduced glutathione (GSH) and lipid peroxidation (LPO). In the liver, the level of metallothionein (MT) and carbonyl proteins (PC) was also determined. Histopathologies were determined in the gills, hepatopancreas and kidneys. The results showed that the accumulation of metals in fish in the hepatopancreas > kidneys > gills > muscles. Fe and Zn were the metals that most accumulated. While the biochemical markers showed that in the gills only SOD (0.1 g L-1) had a significant decrease, in the hepatopancreas, the activity of SOD (1 g L-1) and CAT (0.01; 0.1; 1 g L-1) decreased while GPx (1 g L-1) increased. In those exposed, CAT (1 g L-1) and GST (1 g L-1) activity increased, as did the GSH content (0.1 and 1 g L-1). White muscle increased GSH content (0.01 and 1 g L-1) and GST activity (0.01 and 0.1 g L-1) and LPO levels (0.01 g L-1). In the red muscle, there was an increase in LPO (0.1 g L-1) and PC (0.01 and 0.1 g L-1). In the gills, lesions such as hyperplasia of the lamellar epithelium and filament, partial lamellar fusion and necrosis were more frequent after exposure to 0.1 g L-1 of MPASe. In the hepatopancreas, altered alterations in the parenchyma and hypertrophy of hepatocytes were registered, while in the kidneys, nuclear and cellular hypertrophy occurred. The incidence of alterations indicates that the effects generated by MPASe are reversible, however they can become serious if they are more recurrent. Therefore, the need to create regulations that prevent or reduce the emission of this material into the atmosphere is reinforced.